2015
DOI: 10.1177/0305735614568882
|View full text |Cite
|
Sign up to set email alerts
|

Can music reduce anti-dark-skin prejudice? A test of a cross-cultural musical education programme

Abstract: The study examined the impact of a cross-cultural musical programme on young Portuguese adolescents' anti-dark-skin prejudice. A sample of 229 sixth-grade pupils who attended public schools in the area of Lisbon, Portugal, were presented with the Implicit Association Test (IAT) -an instrument that measures the strength with which dark-skinned faces or light-skinned faces are associated with attributes that can be considered as negative or positive, and with a test measuring explicit anti-dark-skin prejudice. H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…Second, it has been suggested that to reduce racial bias effectively, one of the best approaches is to engage individuals in immersive and prolonged interaction with other-race individuals (Neto, da Conceic ßao Pinto, & Mullet, 2016;Pettigrew & Tropp, 2006;Rudman, Ashmore, & Gary, 2001;Shook & Fazio, 2008). However, it might not be possible for young children to have such opportunities, especially for those living in homogeneous racial settings (e.g., in most parts of Asia and Africa, and some parts of the United States, that have no or very few other-race individuals).…”
Section: Discussionmentioning
confidence: 99%
“…Second, it has been suggested that to reduce racial bias effectively, one of the best approaches is to engage individuals in immersive and prolonged interaction with other-race individuals (Neto, da Conceic ßao Pinto, & Mullet, 2016;Pettigrew & Tropp, 2006;Rudman, Ashmore, & Gary, 2001;Shook & Fazio, 2008). However, it might not be possible for young children to have such opportunities, especially for those living in homogeneous racial settings (e.g., in most parts of Asia and Africa, and some parts of the United States, that have no or very few other-race individuals).…”
Section: Discussionmentioning
confidence: 99%
“…A similar study, conducted with young White U.S. children, also found that two 45‐minute sessions of pro‐diversity curricula (e.g., race‐related stories, discussion, and art) a week over the course of 8 weeks failed to reduce racial biases (Best, Smith, Graves, & Williams, ). In contrast, the one study to examine this type of curriculum in middle childhood indicated that providing education on the music and culture of racial outgroup members (a total of twenty 90‐minute sessions over the course of 6 months) produced a long‐lasting (more than 2 years) reduction in implicit and explicit skin tone bias (favoring light skin) among Portuguese children (Neto, da Conceiçao Pinto, & Mullet, ).…”
Section: Intergroup Educationmentioning
confidence: 99%
“…Interventions on children could be more effective because implicit preferences are more sensitive to experiences at younger ages (i.e., a critical period) or because adults' associations are more stable since they have accumulated more experiences related to an association over a lifetime. We are aware of only four studies that have experimentally examined change in children's implicit preferences to test these questions (Gonzalez, Steele, & Baron, 2016;Neto, et al, 2015;Vezzali et al, 2011;Xiao et al, 2014). As one example, Neto and colleagues' (2015) tested an education program where sixth-graders learned about music and culture from Cape Verde over the course of six months.…”
Section: Implicit Preference Malleability Does Not Necessarily Indicamentioning
confidence: 99%